The Function of Ion Channels and Membrane Potential in Red Blood Cells: Toward a Systematic Analysis of the Erythroid Channelome - von Lindern, Marieke; Egée, Stéphane; Bianchi, Paola; Kaestner, Lars (Frontiers in Physiology, 2022)
Erythrocytes represent at least 60% of all cells in the human body. During circulation, they experience a huge variety of physical and chemical stimulations, such as pressure, shear stress, hormones or osmolarity changes. These signals are translated into cellular responses through ion channels that modulate erythrocyte function. Ion channels in erythrocytes are only recently recognized as utmost important players in physiology and pathophysiology. Despite this awareness, their signaling, interactions and concerted regulation, such as the generation and effects of “pseudo action potentials”, remain elusive. We propose a systematic, conjoined approach using molecular biology, in vitro erythropoiesis, state-of-the-art electrophysiological techniques, and channelopathy patient samples to decipher the role of ion channel functions in health and disease. We need to overcome challenges such as the heterogeneity of the cell population (120 days lifespan without protein renewal) or the access to large cohorts of patients. Thereto we will use genetic manipulation of progenitors, cell differentiation into erythrocytes, and statistically efficient electrophysiological recordings of ion channel activity.